Lipopolysaccharide-induced resistance in mice against ascending urinary tract infection with Klebsiella pneumoniae - Chathley, U C; Sharma, S; Chhibber, S (Folia microbiologica, 1996)
Protective effect of the lipopolysaccharide (LPS) antigen of Klebsiella pneumoniae was tested against ascending-mode urinary tract infection in BALB/c and LACA strains of mice. LPS was given by two different routes; LPS was found to be protective (whatever the application route) since colonization with the challenge organism was significantly lower in both cases as compared with unimmunized mice. A maximum decrease in bacterial count in the kidney of LPS-treated animals was observed on challenge after a 4-d treatment.
Keywords: infekce močového ústrojí; Adjuvants, Immunologic; lipopolysacharidy; adjuvancia imunologická; Lipopolysaccharides; Female; Klebsiella pneumoniae; myši inbrední BALB C; Klebsiella Infections; zvířata; myši; infekce bakteriemi rodu Klebsiella; časové faktory; Mice; ženské pohlaví; Animals; Urinary Tract Infections; Time Factors; Mice, Inbred BALB C